Efficient Nonorthogonal Multiple Access: Cooperative Use of Distributed Space-Time Block Coding; IEEE Vehicular Technology Magazine; Vol. 13, iss. 4 - Dzhamal M. N. Mukhammad Nasar; Khasan S. A. Said Ali; Dzhayakodi (Jayakody) Arachshiladzh D. N. K. Dushanta Nalin Kumara; Rodriges D. Dzhoel (2018, 2018)
Title screen